C14 A PROMISING SURGICAL TECHNIQUE IN PATIENTS WITH ATRIAL FUNCTIONAL MITRAL REGURGITATION: HYPER–DOWN–SIZING ANNULOPLASTY. (18th May 2022) - Innelli, P; Prestipino, F; Manzan, E; Telesca, M; D'Ascoli, R; Paternoster, G; Stabile, E; Luzi, G
Abstract: Objective: Atrial functional mitral valve regurgitation is a less common form of functional mitral regurgitation with normal leaflet motion and morphology, preserved dimension and function of left ventricle, associated with atrial fibrillation ad/or left atrial dilatation. Several factors are involved into the etiology, such as mitral annular dilation and insufficient leaflet remodeling, atriogenic leaflet tethering, loss of annular saddle shape and contractility, changes in heart rate. Methods: Eleven consecutive patients with atrial functional mitral regurgitation, mean age 65 ± 12 years, normal left ventricle dimension and ejection fraction greater than 50% underwent mitral valve repair via right mini–thoracotomy in case of isolated mitral and tricuspid valve surgery or via median sternotomy in case of combined procedures. Concomitant procedures include tricuspid valve repair in 1 patient and coronary artery bypass in 5 patients. All patients presented an increased dimension of left atrium (mean left atrial volume: 90 ± 23 ml); mitral annular dimension was investigated with trans–esophageal echocardiography before operation. In all patients was implanted a downsized complete rigid annuloplasty ring with asymmetrical design of two sizes smaller respect to measured intercommissural distance. Clinical outcomes of patients and echocardiographic findings related to mitral regurgitation recurrence and left ventricle function were followed in the time. Results: At discharge, any patient present a residual mitral regurgitation greater than mild, mean trans–mitral gradient was 2.5 ±2.1 mmHg. During the follow–up period of 24 ± 5 months, the New York Heart Association functional class significantly improved from 2.5 ± 0.4 to 1.5 ± 2.1. In three patients occurred cardiac rhythm disturbances requiring hospital stay, only one patient developed a greater than mild mitral regurgitation, reoperation was not becessary in any case. Left atrial volume decreased from 90 ± 23 ml to 58 ± 30 ml. Conclusions: Mitral annuloplasty with downsized ring is a safe and effective procedure in patient with atrial functional mitral regurgitation in the same way of patient with functional mitral regurgitation due to ventricular dilation and tethering. The comforting clinical and echocardiographic outcome in our small group of patient encourage future studies in this particular group of patients.